1996
DOI: 10.1046/j.1365-2249.1996.d01-836.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemoattractant activity of rheumatoid synovial fluid for human lymphocytes is due to multiple cytokines

Abstract: SUMMARYThe majority of synovial fluids from 29 rheumatoid arthritis patients were strongly attractive for normal blood lymphocytes judged by assays of polarization and collagen gel invasion. While rheumatoid synovial fluids contained IL-15, IL-8, monocyte chemotactic protein-1 (MCP-1) and macrophage inflammatory protein-1® (MIP-1®) at levels sufficient to attract lymphocytes, inhibition of the activity of any single cytokine using specific antibody did not abolish the activity of the fluid. However combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Targeting chemokines with antibodies or binding proteins as well as targeting chemokine receptors has been attempted as a therapeutic strategy (Gong et al, 1997;Ogata et al, 1997;Plater-Zyberk et al, 1997;Barnes et al, 1998;Halloran et al, 1999;Matthys et al, 2001;Podolin et al, 2002;Yang et al, 2002) However, the overwhelming complexity of these signaling molecules (multiple chemokines, chemokine receptors, and redundancy) is a significant hurdle. Polychemokine (Carter, 2002) or combinations of different chemokine (al Mughales et al, 1996) antagonists have been suggested, but there may be chemokines that act as an agonist at one receptor and an antagonist at another (Xanthou et al, 2003). Despite this complexity, these chemokine receptors and ligands represent a tantalizing therapeutic target because of their integral role in the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting chemokines with antibodies or binding proteins as well as targeting chemokine receptors has been attempted as a therapeutic strategy (Gong et al, 1997;Ogata et al, 1997;Plater-Zyberk et al, 1997;Barnes et al, 1998;Halloran et al, 1999;Matthys et al, 2001;Podolin et al, 2002;Yang et al, 2002) However, the overwhelming complexity of these signaling molecules (multiple chemokines, chemokine receptors, and redundancy) is a significant hurdle. Polychemokine (Carter, 2002) or combinations of different chemokine (al Mughales et al, 1996) antagonists have been suggested, but there may be chemokines that act as an agonist at one receptor and an antagonist at another (Xanthou et al, 2003). Despite this complexity, these chemokine receptors and ligands represent a tantalizing therapeutic target because of their integral role in the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…206 The presence of multiple chemoattractants in synovial fluid, including IL-15, IL-8, MCP-1, and MIP-1␣, suggests some redundancy in the factors responsible for T-cell extravasation into RA synovial membranes. 205,207 Indeed, recent work has also documented a role for IL-17 208,209 and IL-18 210 in the pathophysiology of this disease, highlighting the complexity of the cytokine cascades at work in RA. Subsequent studies also demonstrated that IL-15-activated T cells from RA patients stimulated macrophage cell lines and primary monocytes/macrophages to produce TNF-␣ in vitro.…”
Section: Role Of Il-15 In Autoimmune and Inflammatory Diseasementioning
confidence: 99%
“…Interleukin-8 (IL-8), MIP-1alpha and MCP-l have been implicated in rheumatoid arthritis (RA), while MIP-1alpha has been detected in synovial arthritis (12,13). Osteoblastic cells cultured from patients with rheumatoid arthritis or osteoarthritis exhibit strong induction of MCP-1, MIP1alpha and IL-8 (14).…”
Section: Expression Of Chemokines By Osteoblastic Cellsmentioning
confidence: 99%